Neurofilamentopathy in Neurodegenerative Diseases - Liu, Quan; Xie, Fang; Alvarado Diaz, Abdiel; Smith, Mark A.; Moreira, Paula I.; Zhu, Xiongwei; Perry, George (2011)
Neurofilament protein alterations are found in many neurodegenerative diseases, such as amyotrophic lateral sclerosis, Parkinson, Alzheimer, and Charcot-Marie-Tooth. Abnormal modifications of neurofilament, such as mutation, oxidation and phosphorylation, are linked to the disease-related alteration. In this review, the most recent discovery and central arguments about functions, pathological modifications, and genetic mutations related to neurofilaments in neurodegenerative diseases is presented.